Genetic diversity of escherichia coli isolated from birds and bats by using pulsed field gel electrophoresis (PFGE) - Larmina, anak Brown (Universiti Malaysia Sarawak (UNIMAS), 2012)
Escherichia coli (E. coli) belongs to the family of Enterobacteriaceae. E. coli can be found in animals such as birds and bats which cause zoonoses. In this study, a total of 22 isolates of E. coli were used which 11 isolates from birds in Kuching; 6 isolates from broiler chicken and 5 isolates from soil while another 11 isolates were bats from different habitats; 2 isolates from Bukit Aup Sibu, 3 isolates from Nanga Merit Kapit, 4 isolates from Kubah National Park and 2 isolates from Matang Wildlife Centre. The E. coli isolates digested with XbaI generated 6 to 13 bands with sizes of approximately 54.7-668.9 kb. The PFGE profiles were further analysed by using the RAPDistance program and a dendrogram was constructed based on the difference of genetic distance. In this study, the genetic diversity of E. coli isolated from birds and bats was determined from the analysis. Among these samples, the isolates from broiler chicken and soil were more diverse compared to isolates of bats.